A Critical Assessment of Community-Based Tourism Practices in Nglanggeran Ecotourism Village, Indonesia - Ristiawan, Rucitarahma; Tiberghien, Guillaume (Journal of Indonesian Tourism and Development Studies, 2021)
This study investigates the strategic managerial practices to overcome the developmental challenges of CBT in the Nglanggeran Ecotourism Village in Yogyakarta, Indonesia. It evaluates, in particular, the CBT impacts on community economic well-being, socio-cultural development, and environmental sustainability. A qualitative case study approach based on semi-structured interviews with key stakeholders involved in the planning and development of the village was employed to assess the benefits and challenges of CBT practices and their compatibility with sustainable community development. Results indicate that despite new employment opportunities and an increase in environmental conservation efforts, CBT planning and development in the village led to unequal distribution of economic benefits induced by conflicts within the community, uneven participation opportunities of the local community in tourism, and incompatibility in fulfilling individual's need for sustainable community development. Keywords: CBT Practices, Ecotourism Village, Sustainable Community Development.